Effect of a combined machining/burnishing tool on the roughness and mechanical properties. (28th August 2013) - Mezlini, S.; Mzali, S.; Sghaier, S.; Braham, C.; Kapsa, Ph.
ABSTRACT Burnishing is a cold working surface treatment process in which plastic deformation of surface irregularities occurs by exerting pressure through a very hard and a very smooth roller or ball on a surface to generate a uniform and work‐hardened surface. This treatment occurs generally after the machining process. In this study, a new combined machining/burnishing tool is designed and is fabricated. This tool allows for generating simultaneously the machining (turning) and the burnishing of the cylindrical surface using a turning machine. First, turned surfaces at different conditions, sketches, finishing and half finishing were performed using only the cutting tool. The evolutions of a surface roughness parameter and the technological time relative to every test condition have been investigated. Second, using the combined machining/burnishing tool at coarse conditions, the evolutions of the surface roughness and the technological time have been also investigated. A comparison among the parameters obtained under different machining conditions and those obtained using the combined machining/burnishing tool has been carried out. Moreover, the analyses of the layers obtained on the combined machined/burnished surface have shown that the burnishing process induces compressive residual stresses on the subsurface treated specimens. Copyright © 2013 John Wiley & Sons, Ltd.